The Impact of Natural Gas and Oil for the Economy of Azerbaijan - Gülter, Merve (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This thesis examines the role of oil and natural gas resources in the world economy and the impact of natural gas and oil trade for the economy of Azerbaijan. Because of increasing demand of natural gas and oil supply are one of the most important and strategic energy security issues for the countries who don’t have their own energy sources. They inevitably became huge importers of natural gas and oil. Region of Caspian is one of the richest regions in terms of natural gas and oil, has always been important exporters for European Union and Turkey. Azerbaijan has been an important exporter of oil and natural gas which is located in the Western Caspian Region, as the need for natural gas and oil increases, Azerbaijan became significantly important for European Union countries and also for Turkey, and they are now constructing better relations, creating new projects for the new long-term plans. Southern Gas Corridor (SGC hereafter), is a result of good relations with huge importers of Azerbaijan’s natural gas. The SGC is an attempt of European commission for a gas supply route from Caspian to Middle East and to Europe. The aim of Southern Gas Corridor is to decrease EU’s dependency on Russian gas and to diversify the gas routes in order to assure the reliability of gas supply as well as to safeguard the gas delivery for the next decades. SGC has changed the monopolistic power of Russia and led Azerbaijan and Turkey to be the game player in natural gas trade.

ÖZ: Bu tez, doğal gaz ve petrol kaynaklarının dünya ekonomisindeki rolünü ve doğalgaz ve petrol ticaretinin Azerbaycan ekonomisine etkisini incelemektedir. Artan doğalgaz talebi nedeniyle petrol arzı, kendi enerji kaynaklarına sahip olmayan ülkeler için önemli ve stratejik enerji güvenliği konularından biridir. Kaçınılmaz olarak doğalgaz ve petrolün büyük ithalatçıları haline geldiler. Doğalgaz ve petrol açısından en zengin bölgelerden biri olan Hazar Bölgesi, Avrupa Birliği ve Türkiye için her zaman önemli ihracatçılar olmuştur. Azerbaycan, Batı Hazar Bölgesi'nde yer alan önemli bir doğalgaz ve petrol ihracatçısı olmuştur, doğalgaza ve petrole olan ihtiyaç arttıkça, Azerbaycan Avrupa Birliği ülkeleri ve Türkiye için de önemli hale gelmiştir ve giderek daha iyi ilişkiler inşa etmektedir , yeni uzun vadeli planlar için yeni projeler yaratmak önemli hale gelmiştir. Güney Gaz Koridoru (diğer adıyla SGC), Azerbaycan doğalgazının büyük ithalatçılarıyla iyi ilişkilerin bir sonucudur. Güney Gaz Koridoru, Avrupa Komisyonu'nun Hazar'dan Ortadoğu'ya ve Avrupa'ya gaz tedarik güzergahı oluşturma girişimidir. Güney Gaz Koridoru'nun amacı, AB'nin Rus gazına olan bağımlılığını azaltmak ve önümüzdeki yıllar içinde gaz arzının güvenilirliğini sağlamak ve aynı zamanda gaz dağıtımını güvence altına almak için gaz yollarını çeşitlendirmektir.
Master of Science in Energy Economics and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Supervisor: Prof. Dr. Vedat Yorucu
Keywords: Thesis Tez